Penerapan dan Pengaplikasian Metode Recorded Material Untuk Listening Skill dalam Kegiatan “English Day” Di MA Sunan Giri - Rahadianto, Piping (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
This Program called “Pengabdian kepada Masyarakat”, this is the program with the target of the research are teachers and students at MA Sunan Giri, Gondang, Tulungagung. The purpose and benefits of this programs is to run and use a new material in teaching and learning by teachers, especially teachers who teach English subjects in order to apply easy methods in Listening. This research apply the new media such as recorded material in application of listening aspect. This material or in this research called recorded material consist of several listening material in audio and audio visual . By practicing and applying this material student can easily learn English especially in listening aspects. The students can learn English by using recorded materials in several types of listening media. With this method they can fell fun and enjoy during the classroom activity. While this methods is interactive and interesting to applied.